How is physical activity measured in lung cancer?A systematic review of outcome measures and their psychometric properties. Issue 2 (February 2017) - Edbrooke, Lara; Denehy, Linda; Parry, Selina M.; Astin, Ronan; Jack, Sandy; Granger, Catherine L.
ABSTRACT: Physical activity (PA) levels are low in patients with lung cancer. Emerging evidence supports the use of interventions to increase PA in this population. We aimed to (1) identify and synthesize outcome measures which assess PA levels in patients with lung cancer and (2) to evaluate, synthesize and compare the psychometric properties of these measures. A systematic review of articles from searches was conducted of five electronic databases and personal records. Eligible studies were those which assessed PA using either performance‐based or patient‐reported measures. For aim 2, studies identified in aim 1 reporting on at least one psychometric property (validity, reliability, responsiveness or measurement error) were included. Two independent reviewers assessed eligibility and risk of bias with the COnsensus‐based Standards for the selection of health status Measurement INstruments. Thirty‐four studies using 21 different measures of PA were identified. Seventeen studies used performance‐based measures. The Godin Leisure Time Exercise Questionnaire (GLTEQ) was the most frequently used patient‐reported measure. Psychometric properties were reported for 13 of these measures and most frequently for movement sensors. Two studies reported on properties of the GLTEQ. Quality ratings for risk of bias were low. There is significant heterogeneity amongst studies regarding method of PA measurement along the lung cancer continuum. Greater consensus could be achieved by using a consensus approach such as a Delphi process. Future studies should include assessment of psychometric properties of the measurement tool being used. Currently, it is recommended where feasible, both performance‐based and patient‐reported measurements of PA should be undertaken.